High-resolution quasi-distributed temperature and pressure sensing system for deep-sea reservoir monitoring. (August 2022) - He, Xiangge; Xie, Shangran; Gu, Lijuan; Liu, Fei; Zhang, Min; Lu, Hailong
Abstract: The ocean contains rich oil and gas resources such as natural gas hydrate and there is an urgent need to develop tools for in-situ and continuous monitoring of the reservoir with a high resolution in the mining and development procedure. Here we report a state-of-the-art quasi-distributed temperature and pressure sensing system targeting at reservoir monitoring in deep-sea environment. The system contains a quasi-distributed temperature sensing cable, an optical-fiber-based pressure gauge and an interrogator. The temperature sensing cable contains in total 32 fiber Bragg gratings (FBGs) covering a sensing length of ∼ 120 m. The cabled FBG sensor array has been calibrated during its on-site installation in seawater showing a measurement accuracy of ± 0 . 05 ° C along with a resolution of 0.009 °C. An unique Fabry–Perot cavity structure and an optimized demodulation algorithm are designed to realize the pressure gauge, achieving a pressure sensitivity as high as 142.3 nm/MPa, corresponding to a pressure measurement accuracy of ± 1.6 kPa, together with a temperature cross-sensitivity as low as 1.2 kPa/ ∘ C. A tailored sealing procedure is presented to achieve a pressure resistance up to 30 MPa for the entire sensing system, corresponding to an accessible depth of 3000 m underwater. The proposed sensing system demonstrates its ability to continuously track temperature and pressure variation in sea water, representing as an advanced toolkit for energy resources monitoring in marine condition and for deep-sea exploration. Highlights: Temperature and pressure sensing system for monitoring the deep-sea reservoir. A scheme to calibrate the long-covering temperature sensing cable in the seawater. The entire system can work at 3000 m underwater with a tailored sealing procedure. On-site construction demonstrates the functionality and performance of the system.